If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1x + -2 = 34 Reorder the terms: -2 + 4x + -1x = 34 Combine like terms: 4x + -1x = 3x -2 + 3x = 34 Solving -2 + 3x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 34 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 34 + 2 3x = 34 + 2 Combine like terms: 34 + 2 = 36 3x = 36 Divide each side by '3'. x = 12 Simplifying x = 12
| 3bc=12+9bc | | s+808=57 | | -(7-4x)=7 | | 114=2u | | f29=7 | | 11x+11=4x+158 | | 42+5x=9-8x | | v+66=993 | | 6*8=0 | | 284-7x=38x+24 | | 7x+2x-3=5x+9 | | q+407=73 | | -19x-21=35-x | | xy=29 | | 20x^2+60x+45=0 | | q+ -407= -73 | | 3x+1=6x-2 | | r+450=996 | | 4-x=15 | | d-732=-485 | | 630-7x=3x | | 3x+69=8x+12 | | 2+(x-7)+1=7 | | -28-7=10x+23 | | x^6=1.4 | | 2+(x-3)+1=7 | | 35=7d | | 11-t=21 | | 40x^2+20x=0 | | 11=m+6 | | 125=20y-5(15-y) | | 370=m-72 |